Preparation and Characterization of Binary Organogels via Some Azobenzene Amino Derivatives and Different Fatty Acids: Self-Assembly and Nanostructures. (11th June 2014) - Guo, Haiying; Jiao, Tifeng; Shen, Xihai; Zhang, Qingrui; Li, Adan; Gao, Faming
Abstract : In present work the gelation behaviors of binary organogels composed of azobenzene amino derivatives and fatty acids with different alkyl chains in various organic solvents were designed and investigated. Their gelation behaviors in 20 solvents were tested as new binary organic gelators. It showed that the length of alkyl substituent chains and azobenzene segment have played a crucial role in the gelation behavior of all gelator mixtures in various organic solvents. Longer alkyl chains in molecular skeletons in present gelators are favorable for the gelation of organic solvents. Morphological studies revealed that the gelator molecules self-assemble into different aggregates from lamella, wrinkle, to belt with change of solvents. Spectral studies indicated that there existed different H-bond formation and hydrophobic force, depending on different substituent chains in molecular skeletons. The present work may also give new perspectives for designing new binary organogelators and soft materials.